Pengaruh Digitalisasi Ekonomi Terhadap Pertumbuhan Ekonomi Syariah Di Indonesia - Muhammad Ash-Shiddiqy; Makhrus Munajar; Muhammad Ghafur Wibowo (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This study aims to determine the effect of economic digitalization on sharia economic growth in Indonesia. This research uses a literature review method with a descriptive qualitative approach. The qualitative method is a research method based on the philosophy of postpositivism, used to examine the condition of natural objects. Secondary data was obtained through a literature study in which the object of research was journals, books, articles and previous studies that were relevant and related to the situation being studied. Other secondary data sources used to support this research are internet services, magazines, and news related to economic digitalization. The results of this study found that economic digitalization on sharia economic growth has a significant and positive influence. This can be interpreted that Islamic economic growth is influenced by technological developments. As technology develops, it has the potential to increase sharia economic growth in Indonesia